2017
DOI: 10.1371/journal.ppat.1006261
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitously expressed Human Beta Defensin 1 (hBD1) forms bacteria-entrapping nets in a redox dependent mode of action

Abstract: Ever since the discovery of endogenous host defense antimicrobial peptides it has been discussed how these evolutionary conserved molecules avoid to induce resistance and to remain effective. Human ß-defensin 1 (hBD1) is an ubiquitously expressed endogenous antimicrobial peptide that exhibits qualitatively distinct activities between its oxidized and reduced forms. Here, we explore these antimicrobial mechanisms. Surprisingly, using electron microscopy we detected a so far unknown net-like structure surroundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 35 publications
4
77
0
Order By: Relevance
“…Current evidence points to key aspects of the mechanism of action of human defensins being conserved across species . Human α‐defensin 6 and β‐defensin 1 have both been demonstrated to fibrilize in vivo to form nanonet traps that hinder the mobility of bacteria, however, the oligomerization triggers and the required components have not been clearly identified. Furthermore, we recently demonstrated that human β‐defensin 3 contains a motif that binds PIP 2 to mediate tumor cell permeabilization similar to that of the plant defensins .…”
Section: Resultsmentioning
confidence: 99%
“…Current evidence points to key aspects of the mechanism of action of human defensins being conserved across species . Human α‐defensin 6 and β‐defensin 1 have both been demonstrated to fibrilize in vivo to form nanonet traps that hinder the mobility of bacteria, however, the oligomerization triggers and the required components have not been clearly identified. Furthermore, we recently demonstrated that human β‐defensin 3 contains a motif that binds PIP 2 to mediate tumor cell permeabilization similar to that of the plant defensins .…”
Section: Resultsmentioning
confidence: 99%
“…bacter baumannii. Conversely, Gram-positive bacteria were resistant against hBD1ox (10,11), which indicates that hBD1ox activity may target a mechanism that is specific to Gram-negative bacteria. Interestingly, under anaerobic conditions, the hBD1ox completely lost its antimicrobial activity ( Fig.…”
Section: Figmentioning
confidence: 99%
“…Previous data from our group demonstrated that hBD1red is active against Grampositive and Gram-negative bacteria by targeting mainly the bacterial membrane and trapping bacteria in a net structure (11). Due to the different activity spectra of hBD1red and hBD1ox under various environmental conditions, we here aimed to investigate whether the redox-active periplasm of Gram-negative bacteria contributes to the observed difference in hBD1 activity.…”
mentioning
confidence: 97%
See 2 more Smart Citations